2021
DOI: 10.1016/j.jiac.2021.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of Japanese patients with moderate to severe COVID-19

Abstract: Introduction: Although several reports on the risk factors for severe disease of COVID-19 already exist, reports on effective early indicators are still limited, especially from Japan. This study was conducted to clarify the patient's characteristics whose disease progressed to severe status. Methods: The medical records of all consecutive 300 Japanese patients hospitalized at our institution between February and November 2020 were retrospectively reviewed. The clinical characteristics were evaluated to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In our study group, serum CRP levels correlated significantly with the severity of disease, presence of cardiovascular diseases, need of oxygen therapy and computer scan severity. Otoshi et al (2021) demonstrated that age and CRP were independently associated with COVID-19 severity in Japanese patients [ 27 ]. Patients with cardiovascular comorbidities have elevated levels of CRP, and they are more likely to display a systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study group, serum CRP levels correlated significantly with the severity of disease, presence of cardiovascular diseases, need of oxygen therapy and computer scan severity. Otoshi et al (2021) demonstrated that age and CRP were independently associated with COVID-19 severity in Japanese patients [ 27 ]. Patients with cardiovascular comorbidities have elevated levels of CRP, and they are more likely to display a systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed this issue. 7,39,40 During the COVID-19 epidemic, patient assessment is critical.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, from January 16, 2020 (the day on which the first case was confirmed) to October 4, 2021, there were 1.7 million confirmed cases and 17,927 deaths [ 3 ]. One study in Japan revealed similar risk factors for severe COVID-19 [ 12 ]. Regarding the temporal trends, one study highlighted that patients of the second wave had lower mortality and disease severity and were less likely to have comorbidities than those of the first wave [ 13 ].…”
Section: Introductionmentioning
confidence: 99%